Query Processing Algorithm Based on Neighbor Information in Delay Tolerant Network - Dameng Wu; Jiangbo Qian; Yefang Chen; Yihong Dong (Dianxin kexue)
Different from conventional networks, DTN has several unique characteristics, such as node mobility, loose connectivity, and delay tolerability, etc. As mobile devices have become indispensable in daily life, there emerges a new interesting problem, which is how to take advantage of the portable and powerful facilities to share resources and information. The prevailing approach to process those queries is to use flooding methods because of their quick response and easy maintenance. However, this kind of approaches wastes a huge amount of communication bandwidth and battery power of mobile devices. To tackle this problem, an intelligence accuracy（IA） scheme was introduced to improve network query success rate. The IA scheme mimics natural behavior of human social networking features to promote efficiency of information collection. Experimental results show that the efficiency and effectiveness of the IA approach are as well as its scalability in a volatile environment.